The influence of social, economic and health situation on pupils' education in the Second Republic of Poland on the example of Piotrków Trybunalski and Piotrków District - Andrzej Felchner (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
As a result of numerous factors, including activity of the whole generations of the Poles, in autumn 1918 Poland regained its independence.  Unfortunately, the economic and health situation in the country was very bad. Between 1918 and 1939 numerous changes took place. In spite of this, during the whole period, the residential and nutritional position of the society  was still unsatisfactory. Obviously, it influenced in a negative way mostly children and the youth. A good example of the discussed issue can be Piotrków Trybunalski and its district. Many dwellers of the town lived in single- or two-room flats, mostly without the connection to water and sewage system. The majority of children was insufficiently fed or frequently malnourished. Even worse situation was in Piotrków district, especially in villages. One needs to pay attention to those complicated but meaningful issues while discussing the education and upbringing of children and the youth in Poland, between World War I and World War II.